The Synthesis of Magnetic Nitrogen-Doped Graphene Oxide Nanocomposite for the Removal of Reactive Orange 12 Dye - Norah Salem Alsaiari; Abdelfattah Amari; Khadijah Mohammedsaleh Katubi; Fatimah Mohammed Alzahrani; Faouzi Ben Rebah; Mohamed A. Tahoon (Adsorption Science & Technology)
Herein, we report the nanofabrication of magnetic calcium ferrite (CaFe2O4) with nitrogen-doped graphene oxide (N-GO) via facile ultrasonication method to produce CaFe2O4/N-GO nanocomposite for the potential removal of reactive orange 12 (RO12) dye from aqueous solution. The successful construction of the nanocomposite was confirmed using different characterization techniques including scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform-infrared spectroscopy (FT-IR), and X-ray diffraction (XRD). The magnetic properties were studied using vibrating sample magnetometer (VSM) indicating ferromagnetic behavior of the synthesized materials that facilitate their separation using an external magnetic field after adsorption treatment. The addition of N-GO to CaFe2O4 nanoparticles enhanced the BET surface area from 24 to 52.93 m2/g as resulted from the N2 adsorption-desorption isotherm. The adsorption of the synthesized nanomaterials is controlled by several parameters (initial concentration of dye, contact time, adsorbent dosage, and pH), and the RO12 dye removal on the surface of CaFe2O4 nanoparticles and CaFe2O4/N-GO nanocomposite was reached through the chemisorption process as indicated from the kinetic study. The adsorption isotherm study indicated that the adsorption process of RO12 dye was best described through the Langmuir isotherm approving the monolayer adsorption. According to the Langmuir model, the maximum adsorption capacity for RO12 was 250 and 333.33 mg/g for CaFe2O4 nanoparticles and CaFe2O4/N-GO nanocomposite, respectively. The adsorption capacity offered by CaFe2O4/N-GO nanocomposite was higher than reported in the literature for adsorbent materials. Additionally, the regeneration study indicated that CaFe2O4/N-GO nanocomposite is reusable and cost-effective adsorbent. Therefore, the nanofabricated CaFe2O4/N-GO hybrid material is a promising adsorbent for water treatment.